2020
DOI: 10.1016/j.jvc.2020.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the estrous cycle and pregnancy status on cardiovascular variables in healthy bitches

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…The exact aetiology remains unknown; however, it was speculated to be related to different stresses acquired throughout life such as pregnancies and fluctuating levels of cardioprotective oestrogen (Youssef 2021). The role of oestrogen in the cardiovascular system of dogs however was unclear, while inconsistent findings on changes in the level of heart rate, cardiac output level, and echocardiographic findings during pregnancy made the exact role of hemodynamic stress on the risk of heart disease in dogs remains unclear (Brooks and Keil 1994;Olsson et al 2003;Abbott 2010;Blanco et al 2011;de Souza et al 2017;Ward et al 2020). However, in neutered dogs, although other cardiac parameters were indifferent, higher blood triglyceride (TG) and very-low-density lipoprotein (vLDL) was found compared to intact dogs, implying the lost role of oestrogen in the synthesis of antioxidant and atherosclerosis-preventing high-density lipoprotein (HDL) (Boonyapakorn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The exact aetiology remains unknown; however, it was speculated to be related to different stresses acquired throughout life such as pregnancies and fluctuating levels of cardioprotective oestrogen (Youssef 2021). The role of oestrogen in the cardiovascular system of dogs however was unclear, while inconsistent findings on changes in the level of heart rate, cardiac output level, and echocardiographic findings during pregnancy made the exact role of hemodynamic stress on the risk of heart disease in dogs remains unclear (Brooks and Keil 1994;Olsson et al 2003;Abbott 2010;Blanco et al 2011;de Souza et al 2017;Ward et al 2020). However, in neutered dogs, although other cardiac parameters were indifferent, higher blood triglyceride (TG) and very-low-density lipoprotein (vLDL) was found compared to intact dogs, implying the lost role of oestrogen in the synthesis of antioxidant and atherosclerosis-preventing high-density lipoprotein (HDL) (Boonyapakorn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Los cambios fisiológicos más importantes (por sus consecuencias en los procesos farmacocinéticos) se observan a nivel cardiovascular (Pacheco et al 2013). Éstos tienen un ritmo temporal, siendo máximos al día 40 de la preñez; posteriormente comienzan a descender hasta alcanzar los valores de la hembra no preñada el día 20-30 postparto (Ward et al 2020).…”
Section: Aclaramiento (Clearance (Clb)unclassified
“…The previous studies have demonstrated that hemodynamic adaptations to pregnancy affect maternal echocardiographic variables, increase CO [ 11 ], increase left ventricular wall thickness and left ventricular wall mass [ 25 , 26 ], and increase left ventricular end-diastolic volume and left atrial area throughout pregnancy in women [ 27 ]. The left ventricular free wall in systole increased in normal bitches [ 14 ] and the left ventricular diastolic function changed throughout pregnancy in dogs [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The changes in cardiovascular function associated with pregnancy are relevant to clinical practice because they may be exacerbated in association with cardiovascular diseases, including hypertension [4,5], diabetes mellitus [6], and congenital heart disease [7] and also lead to the development of pre-eclampsia in women [8][9][10]. Physiological heart murmurs commonly develop during pregnancy in dogs [11]. Studies of pregnant dogs have demonstrated that hemodynamic adaptations to pregnancy affect maternal electrocardiographic parameters [12] and echocardiographic variables, particularly an increase in HR and CO [11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation